Implikasi Filsafat Aliran Esensialisme Dalam Budaya Pendidikan Indonesia Di Sekolah Dasar - Idawati Idawati; Al Husnul Khatimah Mz; Nurul Mawaddah (Journal on Education, 2025)
Essentialism is a philosophical school that emphasizes the existence of an essence or essential core in every object, concept, or entity. This school argues that every individual or entity has basic characteristics that determine its identity, which are independent of social context or external changes. Essentialist education includes science, art and everything related to human will. The aim of this research is to determine the influence and implications of essentialism in emphasizing local cultural values, the importance of basic knowledge, and character education which has a positive impact on students' development in facing the challenges of everyday life. The data collection method used was by collecting literature studies in the form of journals and interviewing elementary school teachers at Runiah School to gain a deep understanding of the implications of essentialism in the culture of education in elementary schools. The results of research on essentialism in education encourage the integration of cultural values, basic knowledge including subjects subjects such as mathematics, science, and language. The essentialism approach has a main focus on building student character. There are advantages and disadvantages to this essentialism school. Through this approach, students can develop positive attitudes and good behavior in everyday life while understanding and appreciating the cultural diversity around them and essentialism encouraging the integration of local cultural values, such as mutual cooperation activities, social responsibility, and respect for parents, into the educational curriculum.